Moderate Islam and its Implementation among Indonesian Migrant Workers: A Case Study of Surau Syaichona Moh. Cholil Kuala Lumpur, Malaysia - Djakfar , Fera Andriani; Rofi’i, M.; Hamid, Moh. Abu (International Journal of Islamic Thought and Humanities, 2025)
Religious moderation is a movement that embodies important commitments to maintaining harmonious interfaith relations. The implementation of moderate Islam refers to applying Islam in a balanced manner, neither extreme nor liberal. This study aims to explore religious life, particularly among the congregation of Surau Syaichona Moh Cholil in Malaysia, and how they implement moderate Islam. Most of the congregation members are Indonesian migrant workers (PMI) who have lived in Malaysia for a long time and established the surau as a center for religious activities. This study is descriptive qualitative research that describes the conditions at the location according to the reality on the ground. The study found that the congregation of Syaichona Moh. Cholil Mosque has implemented moderate Islam, as evidenced by four indicators of religious moderation: first, national commitment. The congregation still has a strong sense of patriotism despite having lived in Malaysia for a long time, as evidenced by their continued celebration of Indonesian Independence Day and their love for Indonesian domestic products. Second is tolerance, as the congregation members respect others of different ethnicities and religions. Third, anti-violence, which is reflected in their attitudes and teaching methods that prioritize wisdom and avoid violent behavior, whether verbal or physical. Fourth, adaptability to local culture: the congregation continues to observe Islamic holidays such as Maulid Nabi and participates in local traditions such as distributing food according to local customs.